Genetics of biochemical attributes regulating morpho-physiology of upland cotton under high temperature conditions - Sajid Majeed; Muhammad Tanees Chaudhary; Muhammad Salman Mubarik; Iqrar Ahmad Rana; Muhammad Shaban; Daniel KY Tan; Yinhua Jia; Xiongming Du; Lori Hinze; Muhammad Tehseen Azhar (Journal of Cotton Research, 2024)
Abstract Background Cotton is a strategically important fibre crop for global textile industry. It profoundly impacts several countries' industrial and agricultural sectors. Sustainable cotton production is continuously threatened by the unpredictable changes in climate, specifically high temperatures. Breeding heat-tolerant, high-yielding cotton cultivars with wide adaptability to be grown in the regions with rising temperatures is one of the primary objectives of modern cotton breeding programmes. Therefore, the main objective of the current study is to figure out the effective breeding approach to imparting heat tolerance as well as the judicious utilization of commercially significant and stress-tolerant attributes in cotton breeding. Initially, the two most notable heat-susceptible (FH-115 and NIAB Kiran) and tolerant (IUB-13 and GH-Mubarak) cotton cultivars were spotted to develop filial and backcross populations to accomplish the preceding study objectives. The heat tolerant cultivars were screened on the basis of various morphological (seed cotton yield per plant, ginning turnout percentage), physiological (pollen viability, cell membrane thermostability) and biochemical (peroxidase activity, proline content, hydrogen peroxide content) parameters. Results The results clearly exhibited that heat stress consequently had a detrimental impact on every studied plant trait, as revealed by the ability of crossing and their backcross populations to tolerate high temperatures. However, when considering overall yield, biochemical, and physiological traits, the IUB-13 × FH-115 cross went over particularly well at both normal and high temperature conditions. Moreover, overall seed cotton yield per plant exhibited a positive correlation with both pollen viability and antioxidant levels (POD activity and proline content). Conclusions Selection from segregation population and criteria involving pollen viability and antioxidant levels concluded to be an effective strategy for the screening of heat-tolerant cotton germplasms. Therefore, understanding acquired from this study can assist breeders identifying traits that should be prioritized in order to develop climate resilient cotton cultivars.